The Effect of Sustainability Report Disclosure on Profitability in Banks - Nandika, Rahma Ayu; Abidin, Zaenal (Green Publisher Indonesia, 2025)
This study analyzes the effect of sustainability report disclosure on profitability in the ten largest commercial banks in Indonesia for the 2022-2024 period. Profitability is measured using Return On Asset (ROA), while sustainability report disclosure is assessed from economic, environmental, and social performance based on the Global Reporting Initiative (GRI) Standard. The study used a purposive sampling method with panel data regression analysis using Eviews 10 software. The results of the study show that overall, sustainability reports have a positive effect on the company's profitability. Partially, economic performance and social performance show a significant influence on profitability, while environmental performance shows no significant influence. These findings provide important implications for bank management in developing sustainability strategies and reporting transparency.